Seasonal and ENSO-related interannual variability of subsurface fronts separating West Philippine Sea waters from South China Sea waters near the Luzon Strait. (September 2015) - Chen, Chen-Tung Arthur; Yeh, Ya-Ting; Chen, Yen-Chun; Huang, Ting-Hsuan
Abstract: The Luzon Strait is the main channel connecting the West Philippine Sea (WPS) and the South China Sea (SCS). It has been known that the strait's upper-layer waters have a net tendency to flow into the SCS in winter, whereas its intermediate waters mainly flow out of the SCS year round. A shallow, longitudinal subsurface front separates the WPS Tropical Water and SCS Tropical Water which are characterized by the maximum salinity. This front is located between 119.8 and 121°E, with the WPS Tropical Water extending westward the most in winter during normal periods. During El Niño events, however, the WPS Tropical Water extends westward the most compared with those during normal and La Niña periods. Further, an intermediate-depth front also separates the WPS Intermediate Water and the SCS Intermediate Water at roughly 122°E along 21.75°N. This study reports that this intermediate-depth front is roughly longitudinal across the Luzon Strait from 19°N to 21.75°N. Although it is generally stationary at 122°E, the WPS Intermediate Water extends westward the most in spring whereas in fall it extends westward the least. In spring during El Niño periods and in fall during La Niña periods, the WPS Intermediate Water also extends westward the most. The fact that the front for Subtropical Water is located up to 1.7° west of the front of the Intermediate Water indicates that the front is tilted westward when the depth of the front decreases from the intermediate depth up to subsurface depth. Such a tilt is consistent with the notion that there is a net flux of near surface waters flowing into the SCS, while there is a net flux of intermediate waters flowing out of the SCS. Finally, the tilt is the most significant during El Niño periods and the least apparent during La Niña periods. Highlights: A subsurface front separating the WPS and SCS waters exists in the Luzon Strait. The longitudinal front exists between 50 m and 1350 m but tilts towards the west. The front tilts westward the most/least during El Niño/La Niña periods.